2022
DOI: 10.48036/apims.v18i3.705
|View full text |Cite
|
Sign up to set email alerts
|

Functional Echocardiography (FNECHO): Experience in NICU of A Tertiary Care Hospital

Abstract: Objective: To describe the observational findings of functional echocardiography (FnEcho) in neonatal intensive care unit of a tertiary care hospital by evaluating its frequency of use, characteristics of patients and distribution of heart diseases. Methodology: This Prospective descriptive observational study was done in a tertiary neonatal intensive care unit (NICU) in Rawalpindi, from July 2017 to June 2018. A total of two hundred and twelve neonates admitted to the NICU undergoing echocardiographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Subhani et al [6] also conducted a study in which the prevalence of heart disease was 49.5%, and Arshad et al[7] conducted a study where the prevalence of heart disease was 44.1%. Studies done by Whitehall et al, Subhani et al, and Arshad et al[5][6][7] had a comparable prevalence to our present study, indicating 52.6 %. Whereas studies conducted by Moss et al[8] and Kadivar et al[4] showed a prevalence of heart disease to be 90.2% and 746 %, respectively (Table7).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Subhani et al [6] also conducted a study in which the prevalence of heart disease was 49.5%, and Arshad et al[7] conducted a study where the prevalence of heart disease was 44.1%. Studies done by Whitehall et al, Subhani et al, and Arshad et al[5][6][7] had a comparable prevalence to our present study, indicating 52.6 %. Whereas studies conducted by Moss et al[8] and Kadivar et al[4] showed a prevalence of heart disease to be 90.2% and 746 %, respectively (Table7).…”
supporting
confidence: 87%
“…A study done by Whitehall et al [ 5 ] reported that the prevalence of heart disease was 56.6.%. Subhani et al [ 6 ] also conducted a study in which the prevalence of heart disease was 49.5%, and Arshad et al [ 7 ] conducted a study where the prevalence of heart disease was 44.1%. Studies done by Whitehall et al, Subhani et al, and Arshad et al [ 5 - 7 ] had a comparable prevalence to our present study, indicating 52.6 %.…”
Section: Discussionmentioning
confidence: 99%